PERAN PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KECERDASAN SPIRITUAL (Kajian Studi Literasi Pada Quran Surat Luqman Ayat 16, 17, 18 dan 19) - Andriyani, Wiwik Dyah; Salsabilah, Iis; Mubarok, H E. S; Saripudin, Saripudin; Nurdin, Dudung Ali (Penerbit Widina, Widina Media Utama, 2022)
In fact, every child is born intelligent, carrying their own potential and uniqueness which allows them to become intelligent. Howard Gardner in his book Multiple Intelligences, states that there are eight intelligences in humans, namely: linguistic/verbal/language intelligence, logical religious intelligence, visual/spatial/spatial intelligence, musical/rhythmic intelligence, physical kinesthetic intelligence, interpersonal intelligence, intrapersonal intelligence, and intelligence. naturalist. The task of parents and educators is to maintain the characteristics that form the basis of children's intelligence so that they survive until they grow up, by providing good environmental factors and stimulation to stimulate and optimize children's brain function and intelligence. Religious intelligence peaks in adolescence and early adulthood. Some high-level Religious abilities will decline after the age of 40. Logical religious intelligence is categorized as spiritual intelligence, because of its high support in the success of a person's studies. In the IQ test, logical religious intelligence is given priority. Therefore, religion becomes